Visit Analysis Of Degenerative Hypertensive And Diabetic Millitus Patients Reviewed From The Level Of Anxiety During The Pandemic At The Sukorejo Health Center In Blitar City In 2022 - Panca Radono; Yatimah; Wening Palupi Dewi (Journal of Hospital Management and Services, 2022)
Degenerative diseases are chronic diseases that affect a lot of a person's quality of life and productivity, and regular examinations are needed to increase the success of degenerative disease management. The covid-19 pandemic has affected the anxiety level of degenerative patients (hypertension and diabetes mellitus) to visit regularly so that the level of patient visits has decreased. The purpose of this study was to analyze the visits of degenerative patients with hypertension and diabetes millitus in terms of anxiety levels during the covid-19 pandemic. The type of research used is quantitative with a cross-sectional research design, the population and sample of this study are 600 respondents with the simple random sampling technique so that 60 respondents are obtained. This data collection tool uses questionnaires. Data analysis using the chi square test with a α rate of 5% (0.05).the results of the study were obtained (p = 0.000 > 0.05) or ho received which means that there is no relationship between visits by degenerative hypertension and diabetes mellitus patients in terms of the level of patient anxiety during the covid-19 pandemic at the sukorejo health center, blitar city in 2022.it was concluded that there was no relationship between patient anxiety levels during the covid-19 pandemic and decreased visits by degenerative patients with hypertension and diabetes mellitus. It is recommended to further improve the kie or counseling for patients with degenerative diseases (hypertension and diabetes mellitus) to conduct regular examinations.